Xpert negative means no TB: A mixed-methods study into early implementation of Xpert in Puducherry, India - Newtonraj, Ariarathinam (J Family Med Prim Care, 2019)
INTRODUCTION: Xpert MTB/RIF was implemented in 2016 as the initial diagnostic test for extrapulmonary, pediatric, and human immunodeficiency virus–associated tuberculosis (TB) and as an add-on test for sputum microscopy–negative patients under Revised National TB Control Programme, Puducherry, India. We intended to study the change in TB case notification rates (CNRs) after 2015 and explore the enablers and barriers for implementation of Xpert. MATERIALS AND METHODS: Sequential mixed-methods study, quantitative phase followed by a descriptive qualitative phase (key informant interviews with healthcare providers in the program). RESULTS: The TB (all forms) CNR increased in 2016 followed by a drop to 2015 levels in 2017. There was a reduction in patients notified as sputum-negative pulmonary TB and pediatric TB during 2016–2017. Healthcare providers used a negative Xpert result in ruling out TB among patients who would previously get diagnosed clinically. Perceived benefits of Xpert were efficiency, rapid results, and detecting resistance. Barriers included poor awareness among medical colleges and the private sector, difficulty in motivating sputum microscopy–negative patients for Xpert, and incompletely filled referral forms. CONCLUSION: Xpert-negative results should be interpreted cautiously after clinical assessment. Identified barriers should be addressed to ensure that all eligible undergo testing.